MANAJEMEN HUMAS SEKOLAH DALAM MENINGKATKAN SOSIALISASI PROFIL SEKOLAH MI DARUL ULUM WATES NGALIYAN - Muslikah, Roni; Mulyani, Pamungkas Stiya (AL-QALAM: JURNAL ILMU KEPENDIDIKAN, 2023)
The emergence of various educational models offered in schools today has created a challenge for schools in introducing their schools to the community. So school public relations has an important role as a liaison between the school and the community. Public relations has a big role in introducing the school's profile, vision and mission, programs and the advantages of each school. This research is a qualitative descriptive study. Qualitative research is carried out in natural conditions directly to the data source and the researcher is the key instrument and is descriptive in nature, that is, the data collected is in the form of words. Collecting information uses observation and conducting interviews with related parties. Based on the results of research on school public relations management in increasing the socialization of the school profile at MI Darul Ulum, it can be concluded as follows: 1. In MI Darul Ulum's public relations management, there are three collaborative relationships between schools and the community, namely educational relationships, cultural relationships and institutional relationships. Public relations management techniques include external activities and internal activities. 2. Efforts to socialize the MI Darul Ulum school profile, namely: 1) socialization via print media (school bulletins, calendars, articles, pamphlets and brochures), 2) socialization via social media (Facebook and Instagram), 3) socialization via internet media (website and YouTube), and 4) socialization between institutions (school visits, inter-school competitions, and social activities).